Design of fiber optic sensor fabrication system using electric arc - Liau, Tet Loong (2011)
Fiber optic sensors which become a useful technology connected with the optoelectronic manufacture and fiber optic communications field. The ability of fiber optic sensors to replace the traditional sensors and the sensor applications technology has been improved at this moment such as field and wave measurements, pressure, acoustics, temperature, vibration, humidity and medical measurements. The projects focuses on design of long period grating fabrication system. The fabrication principle of the long period fibre grating is based on the electric are technique. Author is using a simple ways to develop an electric arching driver system by using 12 V from power supply for generating electric arc by using a common car ignition coil. Other than that, author design a whole system of the fabrication with holding fiber optic cable with spark gap and using graphical programming, LabVIEW Software to control the aligner for align the fiber optic cable. Besides that, author was developed connectorization and polishing optical fiber to contribute this project. SLED driver board are used as broadband sources to transmit a wavelength pass through optical fiber and spectrometer are accept the light then graphic display at specific operating software. The results demonstrate that provide grating data in the project. The progress of design, methodology, implementation, testing and measurement are discussed here.